Fabricating polyoxometalates-stabilized single-atom site catalysts in confined space with enhanced activity for alkynes diboration - Yiwei Liu (Nature Portfolio, 2021)
It is of great significance to exert the synergistic effect between single atom and support. Here, the authors prepare polyoxometalates-stabilized single-atom site catalysts in confined space with enhanced activity for alkynes diboration.